KINCIR ANGIN POROS VERTIKAL SEBAGAI ALTERNATIF PENGGERAK POMPA IRIGASI PERKEBUNAN DI DESA KARYAMUKTI - Budi, Firman Santya; Mukhtar, Ihsan Adibil (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
A pump is required by guava plantation at Karyamukti village to meet its irrigation. The pump is rented and its fuel is fossil fuel, so that owner of plantation need cost of operation and rental, which is expensive. The purpose of this activity is to design and manufacturing savonius windmill as an alternative pump drive, in order to give energy alternative, which donât spend money to buy fuel and donât cause pollution. This activity consist of requirement identification at plantation, designing of tool, manufacturing, assembling, testing of tool, and analysis. The result of this activity is worthy to replace fossil fuel pump in guava plantation at Karyamukti village because it can utilize potention of low speed wind.